Formulation of Anti-Acneic Medicated Cream Using Mandarin (Citrus reticulata) Seeds - Areeba Shakeel; Ayesha Zaman; Rehmat Zaman (RADS Journal of Biological Research & Applied Science, 2023)
Acne is an inflammatory skin condition and is caused by Propionibacterium acnes. Citrus reticulata seeds are used for their antioxidant and antimicrobial activity around the world as traditional medicine. The objective of this study was to test the antibacterial activity of Citrus reticulata seeds and the anti-oxidant effect of the seeds on acne patients. The antibacterial susceptibility assay of the water and ethanolic extracts of Citrus reticulata was performed by the agar-well plate method. The extracts were assayed on microbial solutions of Staphylococcus aureus, MRSA, E. coli, Klebsiella, and P.acnes the results showed that seed extracts have essential therapeutic activities. For the study of the efficiency against acne, female volunteers from the age group 20-25 were selected for testing of the 8 prepared samples. Results were calculated by the questionnaire filled out by the volunteers. Most of the samples showed positive results against acne without irritation, peeling, and drying of the skin. The results, hence, showed that Citrus reticulata seeds can be used as a topical treatment for acne patients.